Analysis the Healthy School Campaign in Indonesia: A Health Policy Triangle Approach - Dewi, Ni Made Umi Kartika; Januraga, Pande Putu; Anton, Sri Sulistyawati (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
The School Health Program policy was initiated by the Indonesian government in 2014. However, by 2021, student health service coverage was still suboptimal. The Healthy Schools Campaign Program was introduced in 2022 as an alternative policy to revitalize the School Health Programme. The study aimed to analyze the Healthy School Campaign Program using the health policy triangle framework, which includes actors, content, process, and context. This research uses qualitative methods with secondary data sourced from electronic document searches. The main actors in this policy involve official government institutions, supported by collaboration with non-government partners. Policy selection is based on situational, structural, cultural and international contextual factors. The program content focuses on physical health, healthy nutrition, and student immunization. The conclusion is that the selection of content is influenced by how actors identify health problems in the early stages of policy preparation. Implementation of this program requires a clear collaboration system as a reference for its implementation in educational units. Teacher and parent involvement is also very important to increase the effectiveness and sustainability of the program.